Spatial distribution of available micronutrient status under different land use systems of district Doda, J&K - ALAIE, TAJAMUL AZIZ; GUPTA, RENU; SHARMA, VIKAS (Journal of Soil and Water Conservation, 2020)
A survey was conducted to assess the status of four micronutrients, Zn, Cu, Fe and Mn. Composite samples of surface soil were collected following stratified random sampling method at a depth of 0-15 cm from agriculture as well as barren lands and at a depth of 1 meter from forest and horticulture soils of district Doda of Jammu division. The exact sample collection location was recorded using a handheld GPS receiver. Soil micronutrient maps developed using GPS and GIS will help in improving our understanding regarding nature and extent of micronutrient deficiencies and their response to crop growth and development. The content of micronutrients and their availability to crops vary widely depending upon soil types, land uses, ecology and agroclimatic variability. Zinc was sufficient in major areas of Gandoh, Thathri and in small pockets of Ghat blocks towards north-western sides. Available iron was sufficient in major part of district (90% area). Iron was sufficient in central and north-western areas of Ghat block. Available copper was sufficient in major portions of district. Copper was sufficient in soils of upper Thathri and lower areas of Bhaderwah. Manganese was sufficient in soils of all major parts of the district.